Epidemiology of melanoma in Nikšić, Montenegro’s largest municipality - Popović, Ana (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2025)
Introduction: Melanoma can affect individuals of all ages, and its incidence is increasing among younger populations. Dermoscopy units are highly effective in reducing the number of benign lesions excised in high-risk patients. The aim of this study was to determine the occurrence of melanoma following dermoscopic examinations, the reasons for patient visits, the presence of social inequalities, and the characteristics of confirmed melanoma, including size and localization. Methods: We conducted a retrospective descriptive study of patients examined at the Dermoscopy Unit of the Department of Dermatology at Nikšić General Hospital in Nikšić, Montenegro, from 2017 to 2022 using manual dermoscopy examination. Results: The study comprised 125 patients (74 male and 51 female). The main reasons for dermoscopic examinations were a personal history of atypical nevi and the presence of more than 100 melanocytic nevi. The mean thickness of melanoma in patients younger than 45 years was 0.96 mm, in patients 46 to 65 years old it was 1.08 mm, and in patients over 66 it was 1.38 mm. A statistically significant difference in melanoma localization was observed between sexes: in male patients melanoma occurred significantly more often on the trunk, whereas in female patients it was more frequent on the lower legs. Conclusions: Dermoscopy enhances diagnostic accuracy for skin lesions, benefiting both dermatologists and primary care providers. Effective melanoma prevention strategies include practicing sun protection, performing monthly self-examinations for new or changing moles and birthmarks, and attending regular medical checkups.
Keywords: dermoscopy; dermoskopija; epidemiologija; epidemiology; incidenca; incidence; localization; lokalizacija; melanom; melanoma